2019
DOI: 10.3389/fnint.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Descending Pain Inhibitory System in Electroacupuncture-Induced Analgesia

Abstract: Chronic pain is a major health problem, which can impair quality of life and reduce productivity. Electroacupuncture (EA), a modality of medicine based on the theories of Traditional Chinese Medicine (TCM), presents great therapeutic effects on chronic pain. Its clinical application has gained increasing popularity, and in parallel, more research has been performed on the mechanisms of EA-induced analgesia. The past decades have seen enormous advances both in neuronal circuitry of needle-insertion and in its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 160 publications
(184 reference statements)
1
32
0
1
Order By: Relevance
“…As a modified approach of acupuncture, electroacupuncture (EA) employs electrical stimulation. Besides, many clinical trials have shown that acupuncture or EA stimulation also plays a critical role in the management and therapy of immune-related disorders, such as allergic disorders, infections, autoimmune diseases, and immunodeficiency syndromes ( Wang et al, 2017 ; Lv et al, 2019 ). Nowadays, increasing evidence has shown that the analgesic effects of acupuncture are tightly associated with immune regulation.…”
Section: Introductionmentioning
confidence: 99%
“…As a modified approach of acupuncture, electroacupuncture (EA) employs electrical stimulation. Besides, many clinical trials have shown that acupuncture or EA stimulation also plays a critical role in the management and therapy of immune-related disorders, such as allergic disorders, infections, autoimmune diseases, and immunodeficiency syndromes ( Wang et al, 2017 ; Lv et al, 2019 ). Nowadays, increasing evidence has shown that the analgesic effects of acupuncture are tightly associated with immune regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that electroacupuncture (EA), developed from traditional acupuncture, has been widely used in China and some Asian countries for clinical practice due to its considerable fewer side effects [ 21 , 22 ]. Evidence showed that EA stimulation has an effectiveness on neuropathic pain [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CB 1 receptor antagonism is a promising strategy in the treatment of obesity. However, CNS side effects associated with rimonabant and other CB 1 receptor antagonists emphasized the need for new classes of peripherally acting CB 1 receptor antagonists that do not affect the intricate balance between central and peripheral physiological signaling ( Sharma et al, 2015 ; Lv et al, 2019 ). Ongoing efforts to develop safer selective peripherally acting CB 1 receptor antagonists, potent novel CB 1 receptor antagonists or inverse agonists may eventually result in therapeutics that target CB 1 receptors with reduced CNS side effects ( Sharma et al, 2015 ; Yadav and Murumkar, 2018 ; Khan N. et al, 2019 ; Micale et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of pain has been thoroughly researched by many in-depth papers and reviews ( Loeser and Melzack, 1999 ; Raffaeli and Arnaudo, 2017 ; Chen et al, 2020 ). Among the brain and spinal cord areas, the descending pain modulatory pathway is critical in pain perception and acupuncture analgesia ( Lv et al, 2019 ). This system arises in the PAG, where transmitters are activated that contact the rostroventromedial medulla and project to the raphe nuclei in the brainstem, and to inhibitory synapses in the SDH ( Lai et al, 2019 ; Lv et al, 2019 ).…”
Section: The Descending Pain Modulatory Pathway In Acupuncture Analgementioning
confidence: 99%
See 1 more Smart Citation